Advancing Transformative Social-Emotional Learning Through Group Work with Upper Elementary Students. Issue 1 (2nd January 2023) - Cook, Amy L.; Murphy, Kristin M.
ABSTRACT: Social-emotional learning (SEL) interventions through group work with young students must not only incorporate cultural sustaining practices but also center antiracism. We introduce the Transformative SEL framework to promote positive mental health and youth development, with a focus on cultivating cultural assets, employing action-oriented approaches, and centering antiracist SEL pedagogy as fundamental to group work delivery. We provide an overview of the Building Community Group Curriculum, which elevates civic engagement, cultural assets, and action-based strategies in facilitating transformative SEL group work with upper elementary students. We close with recommendations for school-based group specialists that augment equity-oriented transformative SEL group work.